Pelaksanaan Supervisi Klinis Peningkatan Keterampilan Guru SMK Negeri 1 Tuban dalam Menggunakan Model Blended Learning Sebagai Upaya Mengefektifkan Pembelajaran pada Masa Pandemi Covid 19 - Subandi, Subandi (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
In the first cycle, there were as many as 24 teachers (80% teachers) at SMK Negeri 1 Tuban managed to achieve the minimum completeness of the performance test using the Blended learning model. While the average value in the first cycle reached 79.69. In the second cycle, all teachers (100% teachers) at SMK Negeri 1 Tuban managed to achieve the minimum completeness of the performance test using the Blended learning model, with the average score in the second cycle reaching 87.42. The indicator of success in the performance test is the number of teachers who get the "Complete" category on the skills test using the Blended learning Model, reaching 75% of the total number of teachers. So it can be stated that school action research by applying clinical supervision has succeeded in improving the skills of teachers at SMK Negeri 1 Tuban in using the blended learning model. While the effectiveness of learning, also increased after an increase in teacher skills in utilizing the Blended learning model. The researcher tested this effectiveness in 3 classes that were considered the least effective in the implementation of their learning, namely class XII BKP 1, XI TPm 1, and class X KI. In the first cycle, it was found that learning effectiveness data had increased. The percentage of this increase exceeds the indicator of success in increasing the effectiveness of learning that has been set. 2 classes received "High" predicate, namely class XII BKP 1 and class XI TPm 1. Meanwhile, class X KI received "Very High" predicate for learning effectiveness. While in the second cycle, the effectiveness of learning is increasing in the sampled class. All classes received the "Very High" predicate, namely class XII BKP 1, class XI TPm 1 and X KI. So it can be stated that school action research in increasing the effectiveness of learning by conducting clinical supervision using the blended learning model is successful.